Spatial distribution of biopsy cores and the detection of intra-lesion pathologic heterogeneity. (April 2019) - Calio, Brian P.; Deshmukh, Sandeep; Mitchell, Donald; Roth, Christopher G.; Calvaresi, Anne E.; Hookim, Kim; McCue, Peter; Trabulsi, Edouard J.; Lallas, Costas D.
Objectives: The objective of this study was to determine if spatial distribution of multiparametric magnetic resonance imaging–transrectal ultrasound (mpMRI-TRUS) fusion biopsy cores to the index lesion reveals trends in the detection of intra-lesion Gleason heterogeneity and a more optimal prostate biopsy strategy. Methods: Index lesion was the lesion with longest diameter on T2-weighted (T2W)-MRI. In cohort 1, fusion biopsy cores biopsies were taken in areas in the center of the target as well as 1 cm laterally on each side. For cohort 2, targeted biopsies were taken from the center of the lesion only. Heterogeneity was defined as difference in maximum Gleason score obtained from fusion cores in the center of the index lesion versus cores obtained from the periphery (cohort 1), or any difference in maximum Gleason score obtained from fusion cores targeted to the index lesion (cohort 2) compared with systematic 12 cores TRUS biopsy. Results: Ninety-nine consecutive patients (35 and 64 in cohorts 1 and 2, respectively) with median age (SD) and prostate-specific antigen (PSA) of 66.9 (±5.9) and 9.7 (±8.2) respectively, were included. Age, PSA, Prostate Imaging Reporting and Data System (PI-RADS) score, and preoperative MRI lesion size were not significantly different between cohorts. Gleason heterogeneity was observed at a significantly higher rate in cohort 1 versus cohort 2 (58% versus 24%; p = 0.041). In cohort 1, cores obtained from the center of the lesion had higher Gleason score than cores obtained from the periphery of the targeted lesion in 57% of cases. Conclusions: We demonstrate that there is observable tumor heterogeneity in biopsy specimens, and that increased number of cores, as well as cores focused on the center and periphery of the largest lesion in the prostate, provide more comprehensive diagnostic information about the patient's clinical risk category than taking nonspecific cores targeted within the tumor.